RELATIONSHIP OF C-REACTIVE PROTEIN IN HYPERTENSION PATTIENTS IN JAVANESE AND MALAY TRIBES AT RAMBUNG COMMUNITY HEALTH CENTER, BINJAI CITY - Ice Ratnalela Siregar; Shalsabila Zulkarnain (Poltekkes Kemenkes Medan, 2025)
C-reactive protein is a natural inflammation marker produced by the body when the body experiences inflammation or infection. Hypertension is known to be one of the diseases associated with the risk of cardiovascular disease which can trigger the production of this acute phase protein in the body so that its concentration increases and can be detected by qualitative laboratory examination. Hypertension is influenced by age factors, as age increases, a person is more susceptible to hypertension, therefore those aged 60 years and over or the elderly are very susceptible to this disease. In addition, differences in ethnicity cause differences in customs, culture, and eating habits, it is known that hypertension is a common disease experienced by the Malay Tribe than the Javanese Tribe. Therefore, this study was conducted with the aim of determining the relationship between C-reactive protein in elderly hypertension patients along with a description of the results of C-reactive protein in the differences between the Javanese and Malay Tribes. This type of research used a quantitative descriptive method with sampling using a purposive sample technique. Data processed using Fisher Exact Test analysis and CRP examination carried out using the agglutination method. This study was conducted for one week starting from April 29th to May 4th, 2024 with a sample obtained of 45 samples (total population). Based on the research conducted, the positive CRP results were 4 with 1 coming from the Javanese tribe and 3 from the Malay tribe and there was no significant relationship with the Exact Sig value. (2-Sided) 0.558>0.05.